Tetramethylpyrazine Alleviates Trigeminal Neuralgia by Inhibiting HIF-1α-Mediated Neuroinflammation and Oxidative Stress - Wang, Shizi (Pacific International Journal, 2026)
Objective This study investigates whether TMP alleviates TN by modulating HIF-1α-mediated neuroinflammation and oxidative stress pathways, as predicted by network pharmacology analyses identifying HIF-1α as a potential TMP target. Methods A rat model of CCI-ION was used. Post-surgery, rats were randomly assigned to receive TMP at 20, 40, or 80 mg/kg or CBZ at 50 mg/kg. Mechanical pain thresholds were assessed behaviorally. In the trigeminal ganglion, expression levels of HIF-1α, pro-inflammatory cytokines (IL-1β, TNF-α), and antioxidant enzymes (MnSOD, CAT) were quantified by qPCR and Western blot. Microglial activation, myelin integrity, and oxidative stress (MDA content) were evaluated by IBA-1 immunohistochemistry, Luxol Fast Blue staining, and standard biochemical assays, respectively. Result TMP at 80 mg/kg significantly alleviated mechanical hyperalgesia, with efficacy comparable to CBZ. It suppressed HIF-1α expression and reduced pro-inflammatory cytokines (IL-1β, TNF-α), enhanced antioxidant capacity by upregulating MnSOD and CAT and decreasing MDA, and inhibited microglial activation and demyelination. Conclusion TMP likely alleviates trigeminal neuralgia by inhibiting HIF-1α, leading to coordinated downregulation of neuroinflammation and oxidative stress. These results provide experimental evidence for TMP's multi-target analgesic mechanism and identify HIF-1α as a potential target for treating neuropathic pain.